DESIGNING ERGONOMIC POST-COVID-19 SCHOOL FURNITURE - INCEKARA, Cetin Onder (The South African Journal of Industrial Engineering, 2022)
Inappropriately designed classroom furniture that does not take children’s anthropometric measurements into account has a negative effect on children’s musculoskeletal systems. In this study, which kept Covid-19 pandemic policies in mind, students’ static anthropometric dimensions were measured and their descriptive statistics calculated, using mean, standard deviation, percentiles, and statistical tests, including the t-test and one-way ANOVA. A new design for ergonomically oriented classroom furniture for primary school students is proposed that takes into consideration the measured anthropometric dimensions for students’ safety, health, and well-being, and for post-Covid-19 policies. Given the results of the study, school managements must consider the gender and age of students, and take post-Covid-19 policies/protocols into account when procuring classroom furniture.